A review of strategies for producing chimeric birds. (1st February 2014) - Yan, L.; Gao, J. S.; Rui, L.; Lu, Y. N.; Wan, Z. Y.; Yu, X. X.; Zhang, W. X.; Li, H. T.; Shao, Q.; Zhang, J.; Li, Z. D.
Avian chimeras have been shown to be very useful tools for studying embryonic development. Blastodermal cells form stage X embryos and primordial germ cells (PGCs) are extensively used in chimera production. Intraspecies and interspecies germline chimeras have been successfully produced by transferring blastodermal cells or PGCs into recipient blastoderm at stage X or into the early embryonic blood. The long-term culture system established using pluripotent cells from birds provides an alternative method for preserving the endangered species source and facilitates the manipulation of avian transgenesis. A high rate of donor cell-derived progeny production has always been pursued by germline chimera studies. However, the rate of progeny production was unstable. Different methods have been used in an attempt to improve the efficiency of germline chimera production. Several methods have been shown to greatly enhance the efficiency of donor cell-derived progeny production. In this review, we focus on the strategies used for germline chimera production in birds and discuss the factors and measures affecting the efficiency of obtaining donor cell-derived progeny.